Outrageous Plans for Sensible Ideas: School of the Museum of Fine Arts 2020 Senior Thesis Exhibition - Piascik, Beca; Mitchell-Nockowitz, Margot; Fisher-Berger, Dan; Morse, Michaela; Helwig, Sam; Huntington, Aidan; Agnew, Sam; Rochford, Jacob; Stubis, Halley Sun; Lober, Z; Xaviera, Jhona; Antoniou, Badger; Akumanyi, Ariel; Mahaney, Pat (Tufts Archival Research Center, 2022)
Trying to capture the collective spirit of a show is outrageous in and of itself. The Curatorial Team identified distinct themes for this exhibition and chose to elaborate on them individually. Altogether, these themes result in a show that reflects a year of thesis development by a cohort of extraordinary creatives emerging in the midst of planetary mayhem.